Pengaruh literasi keuangan, inklusi keuangan, kontrol diri, dan teman sebaya terhadap perilaku menabung penggemar K-pop - Hajar, Mahra Fairus Fatami; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2023)
Indonesian youths become part of the world community interested in Korean Pop culture. Korean pop, or K-pop, is a pop music genre from South Korea. The love of K-pop brings out to become fans. K-pop fans have a habit of buying K-pop products, so it desires to save money. This study aims to analyze and determine the effect of financial literacy, financial inclusion, self-control, and peer influence on the saving behaviour of K-pop fans in Java. This study is quantitative research with a population of all K-pop fans on Java Island. The sample in this study is 271 respondents who were selected using purposive sampling and snowball sampling with the characteristics are 18–30 years old, buying K-pop products, and having an account at a bank. The analysis technique is multiple linear regression, using IBM SPSS version 26. This study uses primary data from questionnaires. Data collection was obtained by distributing questionnaires using Google Forms. The results showed that financial inclusion and self-control significantly affected saving behaviour, while financial literacy and peer influence had no effect on saving. Financial inclusion has an impact because more accessible access to financial institutions can increase saving behaviour. More excellent self-control management can make K-pop fans save money for unexpected expenses. The implication of this research is that K-pop fans must improve financial literacy and discuss finances with peers to overcome financial problems in the future.